KONSTRUKSI MAKNA CANTIK DIKALANGAN MAHASISWI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK - Irnawati Marpaung; Cut Rizka Al Usrah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
This paper examines the construction of the meaning of beauty among students of the Faculty of Social and Political Sciences. The focus of this research is on the construction of the meaning of beauty that occurs among female students who use skin care products. The theory of social reality construction by Peter L. Berger and Thomas Luckman was used in analyzing the research data. The research method used is a qualitative approach with descriptive analysis through observation, interviews and documentation. The findings of this study indicate that the construction of the meaning of beauty among female students is that female students understand beauty based on physique. College students think women with white skin and free from acne are beautiful women. The driving factors for the construction of the meaning of beauty are: First, financial compatibility where skin care has become a daily need for female students, but in choosing products, female students also adjust the price and their ability to buy the product. Second, the influence of advertising media where female students are influenced by beauty product advertisements which always display models with white and smooth skin so that female students are interested in buying these products with the aim of making them beautiful like the models in advertisements. Third, the influence of interaction with friends where interaction with friends affects the knowledge and selection of female students in the use of skin care products.Tulisan ini mengkaji tentang konstruksi makna cantik dikalangan mahasiswi Fakultas Ilmu Sosial dan Ilmu Politik. Fokus penelitian ini pada konstruksi makna cantik yang terjadi dikalangan mahasiswi pengguna produk skin care. Teori konstruksi realitas sosial Peter L. Berger dan Thomas Luckman digunakan dalam menganalisis data penelitian. Metode penelitian yang digunakan yaitu pendekatan kualitatif dengan analisis deskriptif melalui observasi, wawancara dan dokumentasi. Temuan penelitian ini menunjukkan bahwa konstruksi makna cantik dikalangan mahasiswi yaitu mahasiswi memahami cantik berdasarkan fisik (outer beauty). Mahasiswi menganggap wanita dengan kulit putih dan terbebas dari jerawat adalah wanita yang cantik. Faktor pendorong terjadinya konstruksi makna cantik yaitu: Pertama, Kesesuaian dengan finansial dimana skin care sudah menjadi kebutuhan sehari-hari para mahasiswi namun dalam memilih produknya para mahasiswi juga menyesuaikan antara harga dan kemampuan mereka dalam membeli produk tersebut. Kedua, Pengaruh media iklan dimana para mahasiswi terpengaruh oleh iklan produk kecantikan yang selalu menampilkan model dengan kulit putih dan mulus sehingga mahasiswi tertarik untuk membeli produk tersebut dengan tujuan agar cantik seperti model dalam iklan. Ketiga, Pengaruh interaksi dengan teman dimana interaksi dengan teman berpengaruh dalam pengetahuan dan pemilihan mahasiswi dalam penggunaan produk skin care.